Kontribusi Konvensi ILO No.100 terhadap Hubungan Industrial di Indonesia - Jim Hidayah Wahid; Eka Saputra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Industrial Relations is a system of relationships that exists between actors in the process of producing goods and/or services, including entrepreneurs, workers/laborers, and the government. This system is based on the values of Pancasila and the 1945 Constitution of the Republic of Indonesia. In relation to industrial relations issues in Indonesia, the ILO Convention plays a very important role in creating harmonious, dynamic and fair industrial relations. The ILO Declaration on fundamental principles and employment rights is a manifestation of the sincere commitment of the ILO and its member countries to respect, enhance and implement the principles and fundamental rights contained in the eight ILO Core Conventions. These rights include freedom of association for employers and workers as well as the right to collective bargaining. Indonesia has ratified all eight ILO Core Conventions and is committed to realizing these standards in its laws and practices. With this aim, Indonesia hopes to maintain conducive industrial relations in Indonesia.